2021
DOI: 10.14336/ad.2021.0513
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles as Pro- and Anti-inflammatory Mediators, Biomarkers and Potential Therapeutic Agents in Multiple Sclerosis

Abstract: Multiple sclerosis (MS) is an autoimmune neurodegenerative disease of the central nervous system (CNS) characterized by multiple demyelinating lesions in the spinal cord and brain. Neuronal disruption caused by myelin loss or demyelination, which may accompany axonal changes, leads to multiple neurological symptoms. They may transiently appear for weeks during periods of disease worsening (relapse) in relapsingremitting form of MS (RRMS). Although a number of genetic, metabolic and environmental factors influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 89 publications
(90 reference statements)
0
14
0
Order By: Relevance
“…EVs have also been reported to cross bodily barriers such as the mammalian blood-brain barrier ( Alvarez-Erviti et al, 2011 ; Dickens et al, 2017 ; Pulliam, Sun, Mustapic, Chawla, & Kapogiannis, 2019 ; Russell et al, 2019 ). Due to the relative clinical inaccessibility of the brain, diseases and conditions of the central nervous system (CNS), including neurodegenerative diseases such as Alzheimer’s and Parkinson’s, present diagnostic, prognostic, and monitoring challenges for which EVs in biofluids are a potential solution ( Campbell & Mocchetti, 2021 ; Coleman & Hill, 2015 ; Manu, Hohjoh, & Yamamura, 2021 ; Thompson et al, 2016 ; Upadhya & Shetty, 2021 ; Vandendriessche, Bruggeman, Van Cauwenberghe, & Vandenbroucke, 2020 ) as a kind of ‘liquid biopsy’: if displaying markers of the cell of origin, EVs and their cargo of proteins, nucleic acids, and more can theoretically be traced back to the parent cells and can serve as indicators of cell and tissue health ( Pulliam et al, 2019 ; Shankar, Balaj, Stott, Nahed, & Carter, 2017 ; Vassileff, Cheng, & Hill, 2020 ). However, realizing the promise of EVs requires highly specific and abundant surface markers that can be used as molecular handles to separate target EVs from the high background of EVs from other cells in biofluids like blood ( Thompson et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…EVs have also been reported to cross bodily barriers such as the mammalian blood-brain barrier ( Alvarez-Erviti et al, 2011 ; Dickens et al, 2017 ; Pulliam, Sun, Mustapic, Chawla, & Kapogiannis, 2019 ; Russell et al, 2019 ). Due to the relative clinical inaccessibility of the brain, diseases and conditions of the central nervous system (CNS), including neurodegenerative diseases such as Alzheimer’s and Parkinson’s, present diagnostic, prognostic, and monitoring challenges for which EVs in biofluids are a potential solution ( Campbell & Mocchetti, 2021 ; Coleman & Hill, 2015 ; Manu, Hohjoh, & Yamamura, 2021 ; Thompson et al, 2016 ; Upadhya & Shetty, 2021 ; Vandendriessche, Bruggeman, Van Cauwenberghe, & Vandenbroucke, 2020 ) as a kind of ‘liquid biopsy’: if displaying markers of the cell of origin, EVs and their cargo of proteins, nucleic acids, and more can theoretically be traced back to the parent cells and can serve as indicators of cell and tissue health ( Pulliam et al, 2019 ; Shankar, Balaj, Stott, Nahed, & Carter, 2017 ; Vassileff, Cheng, & Hill, 2020 ). However, realizing the promise of EVs requires highly specific and abundant surface markers that can be used as molecular handles to separate target EVs from the high background of EVs from other cells in biofluids like blood ( Thompson et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes can be used to communicate between cells and travel large distances in the body. Thus, they can be used to monitor MS disease progression and activity as well as therapeutic treatment [ 141 ]. Exosomes can be released from T cells to regulate antigen presenting cells via miRNAs contained within the exosome [ 142 ] and act as proinflammatory regulators in rheumatoid arthritis, Grave’s disease, and in MS [ 143 , 144 , 145 ].…”
Section: Biomarkers For a Future Bioinformatic Approachmentioning
confidence: 99%
“…Exosomes can be released from T cells to regulate antigen presenting cells via miRNAs contained within the exosome [ 142 ] and act as proinflammatory regulators in rheumatoid arthritis, Grave’s disease, and in MS [ 143 , 144 , 145 ]. EVs are found to be increased in the CSF and plasma of MS patients and have different molecular compositions compared to EVs from healthy individuals [ 141 ]. A study found that patients with RRMS had significantly altered miRNAs compared to controls, specifically an increase in miRNA let-7i in exosomes [ 146 ].…”
Section: Biomarkers For a Future Bioinformatic Approachmentioning
confidence: 99%
“…Multiple sclerosis, characterized by multiple demyelinating lesions of the spinal cord and brain, has a progressive neurodegenerative pattern ( Manu et al, 2021 ; Zahid et al, 2021 ). Berberine has been reported as a potential drug for the treatment of multiple sclerosis.…”
Section: Therapeutic Effects Of Berberine On Neurodegenerative Diseasementioning
confidence: 99%